Desa Wisata Fatumnasi Berdaya: Strategi Pelatihan Bahasa dan Budaya Lokal untuk Peningkatan Sumber Daya Manusia - Langkameng, Oce Antipas; Meluk, Oktoviana Derice; Selan, Dwi Dersmi; Sekoni, Rocky P (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Fatumnasi is renowned for its natural beauty and rich cultural heritage. The community in this village maintains strong kinship, preserves traditional customs, and welcomes visitors as family. The village boasts potential for mountain and cultural tourism, including traditional dances and local cuisine from the Dawan. As a pilot project for sustainable tourism development, the village requires competent human resources to manage these potentials. However, the tourism awareness group in Fatumnasi faces challenges in tourism management, particularly regarding English language skills and knowledge of local wisdom. The Community Service Team from the University of Persatuan Guru 1945 NTT collaborated with Pokdarwis to identify these issues. Together, they agreed to conduct English language training and provide assistance in promoting local cultural products. The goal of this activity was to enhance English proficiency and understanding of local culture to attract more tourists. The results shows that: (a) English for Specific Purposes training was successfully implemented for Pokdarwis in Fatumnasi; (b) Improved understanding among the member of Pokdarwis regarding the history and philosophical elements of each traditional weaving motif. This was evidenced by their ability to create narratives explaining the cultural values behind each motif, which is expected to captivate tourists and encourage longer stays in Fatumnasi.